Mainstreaming climate change adaptation into urban planning—A pragmatic protocol to tackle the implementation gap - Liss, Bethany M.; Wannewitz, Mia; Chaves, Carmeli Marie; Grobusch, Lena C.; Islam, Sonia; Magnaye, Dina C.; Napalang, Ma Sheilah G.; Eugenio, Vincent F.; Garschagen, Matthias (Frontiers in Climate, 2025)
Despite the growing body of scientific literature on mainstreaming climate change adaptation (CCA) into urban planning and numerous implementation guidelines, adaptation remains insufficiently integrated across sectors and scales in urban development, particularly in cities in the Global South. Persisting challenges are conceptual ambiguity, lengthy and overwhelming manuals and guidelines not tailored to planners' needs, and the limited transferability of case study findings especially for cities in the Global South. This study addresses these gaps by developing a pragmatic mainstreaming protocol tailored for urban policymakers and planners to facilitate the mainstreaming of CCA into urban development planning. It provides information and guidance regarding four key elements of mainstreaming: policy formulation, planning, resource allocation and implementation. The protocol was piloted in Metro Manila, the Philippines, focusing on enhancing the integration of upgrading and resettlement as adaptation strategies in urban development planning. They contribute to the ongoing debate on whether mainstreaming of adaptation into general urban planning is more effective than dedicated adaptation policies. This work highlights the need for coherent policies, clear roles, and cross-sectoral collaboration to ensure resilient urban development in vulnerable regions.